Stylistic punctuation of promotional texts - Smetonienė, Irena (Lietuvių kalba, 2013)
The article deals with promotional texts as the genre of advertising allows disclosing the methods that its creators use in seeking to attract the addressee’s attention and persuade them to purchase an item under consideration. Promotional texts are closely related to the style of public media, i.e. that functional style which due to its greater persuasive character acquires the features of all other functional styles, including punctuation. Applying the analytical and the descriptive methods, this article aims at exploring to what extent the semantics of punctuation has developed in advertising and how punctuation marks are used to effectively create information with an emotional and expressive quality. Promotional texts contain no neutral punctuation marks. They have one main function, i.e. an emotional-expressive function. Even when they perform other functions, at the same time they also convey a certain emotional shade of meaning. The exclamation mark, question-mark and ellipsis in advertising mark the greatest number of emotion shades, create suspension, an impression of emotion swings, make the addressee think, evaluate and fill the gaps that have been left. When an advertisement makes use of suspense which is eventually broken and leads to a positive ending, its creators use a combination of several punctuation marks. The semantics of the dash in advertising has also acquired new shades of meaning. A dash gives rise to unexpected nuances of thought, dynamics of text, it marks an emotional pause, burst of feelings; yet, when a dash performs the emotional-expressive function its effect is strengthened by the usage of an exclamation mark. The period, which is traditionally a neutral mark, in advertising is not entirely neutral: in a slogan it occupies the position of an exclamation mark and therefore it obtains emotional character. When performing a compositional function, it gives more flexibility to emphasise different semantic foci; it highlights segmentation, addition (pridūrimas) and distribution (parceliacija). The comma in advertising may be neutral but it can also mark emotional pauses. It performs the expressive function when it separates parentheses, additive clauses or when it highlights rhetorical figures.